Dinâmicas corporais de estudantes de saxofone e considerações de um profissional da Educação Física para a prática do instrumento - Alexandre Vianna Meireles dos Santos (2014)
The subjects "health musician" and the rehabilitation of the use of the body, have been widely discussed by researchers who deal in different areas, such as Medicine, Physiotherapy, Occupational Therapy and the Alexander Technique, among others. However, very few studies have been found, that discuss these issues from the perspective of Physical Education. The present study offers a discussion on how Physical Education professionals can contribute to the promotion of health and prevention of injury in saxophonists. The main themes which are discussed are: an education about the use of the body for the practice of the instrument; control of the music studies; and specic strength training for the performance of the saxophonist.To this end, the performance of four saxophonists were observed by a panel of health professionals (Physical Education, Physiotherapy and Medical), as well as by professionals of re-education of the body (Alexander Technique) and Music teaching (Saxophone). It was found that, during their performances, the saxophonists adopted specic posture techniques for playing the instrument, including left shoulder exion, right shoulder extension, elbows exion and the trunk rotation to the right side. Furthermore, it was observed that their bodies were in constantly movement. These static and dynamic actions occurred in an integrated manner and were inuenced by the ergonomics of the instrument, the type of the strap used by the saxophonists, by the height regulation of the sheet music stand, by the position assumed by their bodies (standing or sitting) and by the specic level of physical development for practicing the saxophone. Considering the physical conditions presented by the research subjects, the interaction of these factors and these static and dynamic actions resulted in cervical protrusion, sway back posture, scapular depression, right shoulder extension, scapulas anterior tilt, shoulders protrusion, thoracic kyphosis and erector spinae muscles well developed (hypertrophied) on left side of thoracic region. The research concludes that, in the role of teacher and educator of the musicians bodies, the Physical Education Professional can avoid those physical adaptations imposed by the practice of the instrument, which are harmful to health, and contribute to health promotion and injury prevention of saxophonists.